Doença meningocócica em crianças: Panorama das hospitalizações e da morbimortalidade na Bahia e macrorregiões, de 2011 a 2020 - Vitória Pinho Lopes Cunha; Nívea Lins de Almeida; Clarissa Cavalcanti Souza; Katia de Miranda Avena (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To describe the epidemiological profile of hospitalizations of children due to meningococcal disease in Bahia and its macro-regions, estimating morbidity and mortality due to the disease. METHODS: This is an ecological, time-series study carried out through the Hospital Information System (SIH/DATASUS), from 2011 to 2020. The variables of interest were gender, age group, ethnicity, character and care regime, and outcome, grouped by year and macro-region in Bahia. RESULTS: There were 431 hospitalizations of children between 0 and 14 years of age due to meningococcal infection, with a predominance of the age group of 0 to 4 years, male, mixed-race, attended on an emergency basis and in a public service regime. Of the hospitalized patients, 91.4% (n=394) were discharged and 8.6% (n=37) died. There was higher mortality and lethality among patients aged between 0 to 4 years. Among Bahia's macro-regions, the East and Central-North had the highest and lowest number of cases of the disease, respectively, while the East and the Far South had the highest mortalities and fatalities. CONCLUSION: The epidemiological profile of meningococcal disease in Bahia follows the global and national trend, with a predominance among boys, brown, aged between 0 to 4 years, whose prevalence, mortality and lethality stand out among the age groups studied. Taking into account the endemic status of meningococcal disease in the state, these results can support and direct specific strategies to combat meningococcus, reinforcing the need for constant preventive actions and epidemiological surveillance, with the establishment of health promotion strategies and better applicability of resources. for the eradication of the disease.